2014
DOI: 10.3892/or.2014.3207
|View full text |Cite|
|
Sign up to set email alerts
|

Increased expression of Lgr5 is associated with chemotherapy resistance in human gastric cancer

Abstract: Abstract. Leucine-rich repeat-containing G protein-coupled receptor 5 (Lgr5), a marker of adult stem cells and cancer stem cells, plays important roles in tumor progression. Furthermore, Lgr5 also contributes to chemoradiotherapy resistance. However, the function of Lgr5 in the prediction of preoperative chemotherapy efficacy has not been reported. We evaluated the potential of Lgr5 in predicting tumor response and overall survival in advanced gastric cancer treated with preoperative chemotherapy. The associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…HER2 IHC was performed as described previously[18]. In brief, tumor specimens were fixed in 10% neutral-buffered formalin overnight and embedded in paraffin blocks.…”
Section: Methodsmentioning
confidence: 99%
“…HER2 IHC was performed as described previously[18]. In brief, tumor specimens were fixed in 10% neutral-buffered formalin overnight and embedded in paraffin blocks.…”
Section: Methodsmentioning
confidence: 99%
“…For GCs, previous studies have reported inconsistent results. Xi et al [24] showed that LGR5-positive patients had a significantly shorter survival time than LGR5-negative patients. On the other hand, Bauer et al [36] suggested that LGR5 mRNA expression was not a prognostic marker in GCs even though LGR5 expression increased in tumors after neoadjuvant chemotherapy.…”
Section: Snu484mentioning
confidence: 99%
“…In colorectal cancers, the prognostic value of LGR5 was extensively studied and found to be statistically related to the reduced overall survival [22]. However, for GCs, only a limited number of studies have investigated LGR5 expression and its relevance in predicting clinical outcomes [17,23,24]. Previously, we specifically identified LGR5-expressing cells in normal gastric mucosa and intestinal metaplastic lesions as well as gastric adenomas by RNA in situ hybridization (ISH) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described the relationship between LGR5 expression and prognosis in gastric cancer [16][17][18][19][20][21]. These reports were inconsistent, however, with several studies drawing statistically insignificant results [17], and in certain cases, completely opposite results [16].…”
Section: Introductionmentioning
confidence: 98%